1979
DOI: 10.1007/bf03006450
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nitrous oxide contamination in a paediatric hospital

Abstract: ANAESTHETIC AGENTS can cause acute "z and chronic 3"4 illness in operating-room personnel and contribute to atmospheric pollution in hospltals. 9 Several professionaP -s and national ~s bodies have proposed guidelines concerning this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Median [interquartile range] 1 h postoperative nitrous oxide concentrations (ppm) in oncology, dental theatre, day surgery unit and MRI suite were: blood, 6 [3][4][5][6][7] [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. .............................................................................................................................................................................................................. Unpaired t-test was applied to determine if there were any significant relationships between blood sevoflurane and nitrous oxide concentration and the type of induction technique, airway management, circuit used or presence of scavenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median [interquartile range] 1 h postoperative nitrous oxide concentrations (ppm) in oncology, dental theatre, day surgery unit and MRI suite were: blood, 6 [3][4][5][6][7] [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. .............................................................................................................................................................................................................. Unpaired t-test was applied to determine if there were any significant relationships between blood sevoflurane and nitrous oxide concentration and the type of induction technique, airway management, circuit used or presence of scavenging.…”
Section: Resultsmentioning
confidence: 99%
“…Sevoflurane and nitrous oxide are used frequently in these circumstances. Studies have shown that exposure to waste anaesthetic gases during paediatric operating lists is high, especially during inhalational induction [1–6]. Previous studies in our hospital have also shown that staff exposure in nonopertaing theatre situations is high, whereas in the operating theatre, exposure was generally found to be within acceptable limits [7].…”
mentioning
confidence: 93%